2001
DOI: 10.1046/j.1365-2109.2001.00538.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of sex and evaluation of ovarian maturation of fish using ultrasonography

Abstract: Ultrasonography is a non-invasive method that can be used to assess sex and maturity of ®sh. This study was conducted to examine the feasibility of using ultrasound images to sex juvenile and mature halibut Hippoglossus hippoglossus (Linnaeus), mature winter Pleuronectes americanus (Walbaum) and yellowtail¯ounder Pleuronectes ferruginea (Storer) and mature haddock Melanogrammus aegle®nus (Linnaeus). In females, both immature and mature ovaries were relatively easy to distinguish, but in males only mature teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 15 publications
0
39
0
Order By: Relevance
“…In contrast, if fish 131191 was male, the same energetic constraints may not limit spawning activity, such that higher frequency rises indicate spawning at will. This hypothesis can be tested in subsequent tagging missions using ultrasonic methods for determining sex developed for Atlantic halibut [43] and applied to Pacific halibut [44]. Potential sex differences may also be examined from these and subsequently tagged fish using fin-clip samples exposed to new genetic approaches [45].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, if fish 131191 was male, the same energetic constraints may not limit spawning activity, such that higher frequency rises indicate spawning at will. This hypothesis can be tested in subsequent tagging missions using ultrasonic methods for determining sex developed for Atlantic halibut [43] and applied to Pacific halibut [44]. Potential sex differences may also be examined from these and subsequently tagged fish using fin-clip samples exposed to new genetic approaches [45].…”
Section: Discussionmentioning
confidence: 99%
“…Fish should be anaesthetized and initial length and body weight recorded and milt expressed to verify sex and gauge sexual readiness. Ultrasound has also been proven to be a useful non-lethal tool to determine sex and ripeness (Martin-Robichaud and Rommens, 2001). A few days after transfer to spawning tanks, fish should be free of symptoms of fright or stress (such as dark skin blotches) or immobility (Billard et al, 1981).…”
Section: Broodstock Collection and Husbandrymentioning
confidence: 99%
“…Previous studies using the ultrasound imaging methodology in fish have focused on reproduction for sex determination (CREPALDI and ROTTA, 2007;MARTIN-ROBICHAUD and ROMMENS, 2001 carcass evaluation using ultrasonography has also been performed. CREPALDI et al (2008) found high correlations between US images and yield traits, such as carcass, head, shank fillet and belly fillet in surubins (Pseudoplatystoma spp.).…”
Section: Discussionmentioning
confidence: 99%